Diet quality scores in relation to fatness and nutritional knowledge in women with polycystic ovary syndrome: case–control study. Issue 11 (21st August 2021) - Bykowska-Derda, Aleksandra; Czlapka-Matyasik, Magdalena; Kaluzna, Malgorzata; Ruchala, Marek; Ziemnicka, Katarzyna
Abstract: Objective: The purpose of the study was to analyse the dietary habits identified by diet quality scores (DQS) in the scope of body fatness (BF) and nutritional knowledge (NK) of polycystic ovary syndrome (PCOS) women. Design: Case–control study. The DQS were accessed by Dietary Habits, and Nutrition Beliefs Questionnaire (KomPAN, The Committee of Human Nutrition, Polish Academy of Science) included food frequency consumption of thirty-three food items and was formulated by six diet indexes: Pro-Healthy-Diet-Index (pHDI-10), Non-Healthy-Diet-Index (nHDI-14), High-Glycemic-Diet-Index-7 (hGIDI-7), Low-Glycemic-Diet-Index-4 (lGIDI-4), High-Sugar-Diet-Index-4 (hSDI-4) and High-Saturated-Fats-Diet-Index-8 (hSFDI-8). The BF was analysed by air displacement plethysmography (BodPod, Life Measurement Inc.). NK was assessed by using the twenty-five 'true or false' statements included in the KomPAN questionnaire. Setting: Poland, Clinical Hospital, Department of Endocrinology, Metabolism, and Internal Diseases. Participants: The study group included 122 PCOS women and 116 age- and socio-economic status-matched healthy controls (CON) aged 17–44 years. Results: Higher BF and lower NK in PCOS women v . controls were observed. PCOS women had a lower pHDI-10 and LGIDI-4 than CON. There was no relation between NK and DQS in PCOS women. The higher NK in the CON group was associated with increased intensity of pHDI-10 and lower frequency of hSFDI-8 levels. Conclusions: Pro-healthy DQS and NK of PCOS women in this study were lower than CON. Professional dietary education might improve dietary behaviours and understanding of the necessity of dietary habits modification in this group. A multidisciplinary approach is needed in the treatment of PCOS women.